An Over View on Nonlinear Partial Differential Equations: Dealing with stiffness in nonlinear partial differential equations using exponential integrators (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Some genuine applications include circumstances where diverse physical wonders following up on altogether different time scales happen at the same time. The halfway differential conditions (PDEs) overseeing such circumstances are ordered as solid PDEs. Solidness is a difficult property of differential conditions (DEs) that forestalls traditional unequivocal numerical integrators from taking care of an issue effectively. For such cases, security (instead of precision) prerequisites direct the decision of time step size to be extremely little. Extensive exertion in adapting to firmness has gone into creating time-discretization strategies to defeat a large number of the limitations of the regular techniques. As of late, there has been a reestablished enthusiasm for exponential integrators that have developed as a reasonable option for managing firmness of DEs. Our consideration has been centered on the unequivocal Exponential Time Differencing (ETD) integrators that are intended to tackle firm semi-straight issues. Semi-direct PDEs can be part into a straight part, which contains the stiffest piece of the elements of the issue, and a nonlinear part, which fluctuates more gradually than the straight part.